The Role of Human Nature and Morality in Cormac McCarthy’s The Road - Neupane, Ravindra (Humanities and Social Sciences Journal, 2022)
This paper has examined how human nature and morals play a role in humanity’s obsession with (post-) apocalyptic literature. Especially, it has analyzed The Road (2006) in light of Literary Darwinism, often known as Evolutionary Literary Study, which has evolutionary psychology as its theoretical foundation. This paper investigates The Road in the context of models of human nature and behavior by adopting a literary Darwinist approach and apocalyptic thought. It is demonstrated that (post-) apocalyptic authors examine human nature and morality when survival is at stake by exploiting both created (cultural) concerns and universal (natural) worries in their dystopian settings. Additionally, it has revealed how vitally evolved aspects of the human mind are to (post-)apocalyptic fiction. Since the creative scenes in these kinds of novels are works of human imagination, they ought to be able to tell us something about the brains behind them, as well as their ethos and motivations. The basic elements of human nature that McCarthy explores are also assessed in terms of how they align with or conflict with fundamental ideas about human nature and morality, though in ways that are constrained and channeled by the author's cultural context, personal needs, and the motivation behind writing about such a post-apocalyptic world. McCarthy’s ethics and ideals as well as the effect McCarthy’s post-apocalyptic world has on readers are examined. Based on the analysis presented in this paper, by emphasizing human nature and the cultural context of the time, as well as by drawing a distinction between culture and nature through the lens of Literary Darwinism, this paper has found that McCarthy’s The Road is profoundly influenced by moral characteristics, human nature, and universal human fears and needs.